The Market Revolution in Bank and Insurance Firm Governance: Its Logic and Limits - David A. Skeel Jr. (Washington University Law Quarterly, 1999)
Exploring the recent trends in banking and insurance from a corporate governance perspective will both shed light on the significance of the new developments and suggest several changes lawmakers might make to improve the current insolvency framework. The Article will focus especially on commercial banks and to a lesser extent on insurance companies, but much of the analysis also applies to other bank-like financial intermediaries.
Keywords: Banking industry; Insurance; Corporate governance; Financial services